Ectopic Pregnancy in a California sea lion (Zalophus californianus) - Seguel, Mauricio; Halaska, Barbara; Johnson, Shawn; Gottdenker, Nicole (Brazilian Journal of Veterinary Pathology, 2016)
Ectopic pregnancies have been rarely reported in animals and little is known in wildlife species regarding the capacity of the placenta to support extrauterine fetal development. An adult, female, free-ranging California sea lion (Zalophus californianus) died suddenly after four weeks in a rehabilitation center. At necropsy, a partially mummified fetus, covered by light-brown membranes occupied the lower third of the abdominal cavity. The maternal uterus was intact and a prominent corpus luteus enlarged the right ovary. The fetal membranes epithelium had immunohistochemical profile identical to normal sea lion placenta but was different from the staining profile of sea lion omentum. The findings in this case suggest that partial placentation occurred in the abdominal cavity, highlighting the potential of otariids placenta to support ectopic fetal development. Acute toxic shock with disseminated intravascular coagulation was considered the most likely cause of death of the adult female sea lion.